A via transgressora da cinematografia: dos experimentalismos aos ambientes imersivos - Menezes, Natália Aly (2012)
It is known that film, like all other arts, is influenced by technological advances. These influences inevitably modify film language. Today, the most obvious and visible interference of digital media on film lies in the possibilities of special effects that these new "tools" bring to the seventh art. However, my object of research has not turned towards that direction, but instead it was directed towards questions concerning the future of cinema, the possibilities of its language introduced by digital media, and especially for the creation of new forms of perception proper to interactive immersive environments. Although this question corresponds to a contemporary state of the art due to the explosion, followed by the consolidation of digital devices in the XXI century, in fact, it has already been studied and experimented since the 1970s and 1980s in the theoretical work of researchers such as Lev Manovich, Bill Seaman, Arlindo Machado, Peter Weibel, Peter Lunenfeld, Jeffrey Shaw, among others. They were all taken as the main sources for my discussions. The trends, which are many, and have received various designations in the direction of a possible future cinema, were discussed in chapter 2. Among them, the one that was studied more closely, that is, the conditions of immersion and the new narrative forms that they introduced, was the object of study of chapter 3. As a basis for these two chapters, chapter 1 discussed the roots of these present trends. These are to be found in experimental cinema and its enfolding along time whose consequences culminated in what, among other names, is being called future cinema